I hate Suzie. Season one [videorecording (DVD)] - Piper, Billie, 1982- (Universal, 2021)
Suzie Pickles, a star on the wane, has her whole life upended when her phone is hacked and a photo of her in an extremely compromising position is released for the whole world to see. Suzie travels through Shock, Denial, Fear, Shame, Bargaining, Guilt, Anger, and Acceptance as she and her best friend and manager Naomi try to hold her life, career, and marriage together in the face of being exposed for who she was in her worst moment.